What drives success in English medium taught courses? The interplay between language proficiency, academic skills, and motivation - Rose, H; Curle, S; Aizawa, I; Thompson, G (Taylor and Francis, 2019)
This article explores the relationship between course performance, English language proficiency, motivation, and academic language skills in an English medium instruction (EMI) university context. It analyses test and questionnaire data from 146 students from an EMI business program at a Japanese university, and follow-up interviews with seven students. Proficiency test and subject exam scores revealed that knowledge of English language and academic English skill were statistically significant predictors of success in EMI, suggesting that lower proficiency students require more targeted language support in order to increase their likelihood of success. A motivation measure did not correlate with higher grades, contradicting research in language learning contexts. Interview data uncovered the multi-faceted nature of ‘success in EMI’ suggesting that students see success as a combination of final grades, lecture comprehension, English language proficiency gains, and long-term career advancement.